Pride Week, Silence and Violence (2015) - Koteska, Jasna (Center for Media and Communications, Faculty of Media and Communications, Belgrade, 2015)
ABSTRACT Pride Week, Silence and Violence (LGBTI in Macedonia, 2013 and 2014) Jasna Koteska The text “Pride Week, Silence and Violence (LGBTI in Macedonia, 2013 and 2014)” by Jasna Koteska analyzes the role of the media in the first ever organized Pride Weeks in the Republic of Macedonia in 2013 and 2014. The text analyses the complex relation between three related processes: silencing the LGBTI community in the media, the rise of the violence in language (derogatory slogans, death threats) to the actual physical outbursts of violence towards the members and the supporters of the LGBTI community in these two years. The text analyses several phenomena related to violence in language and physical violence: space, the gaze and the construction of the image of the “fantasy enemy”.
LGBTI in Macedonia, 2013 and 2014
Keywords: Pride Week; LGBTI; Silence; Violence; Media; Macedonia